COVID-19 in perinatal period: questions and consequences - Tunçel, Duygu; Bilgin, Leyla Karadeniz; İnce, Zeynep and Çoban, Asuman (The Turkish Journal of Pediatrics, 2022)
Background. The effect of COVID-19 infection on newborn babies is not yet clear. Babies born to pregnant women with suspected or proven COVID-19 or babies who had contact with infected people are considered to be at risk. In this review, intrauterine problems that may be caused by COVID-19 infection, delivery room approach, postnatal follow-up, precautions and controversies regarding breastfeeding and vaccination are discussed. Methods. The articles published between March 2020 and June 2021 were searched in Pubmed, Cochrane Library and Google Scholar databases using the keywords COVID-19 and newborn, perinatal period, vertical transmission, pregnancy, breast milk and vaccines. The updated information and recommendations are presented. Conclusions. Our knowledge of the perinatal and neonatal effects of COVID-19 infection changes rapidly. Therefore, close follow-up of the mother-infant dyads is important. Larger epidemiological and clinical cohort studies are needed to better understand the possible implications and long-term outcomes of COVID-19 infection and also maternal vaccination in newborn infants.